1999
DOI: 10.1086/311869
|View full text |Cite
|
Sign up to set email alerts
|

Unidentified Molecular Bands in the Plasma Tail of Comet Hyakutake (C/1996 B2)

Abstract: Unidentified molecular emission bands first observed in optical spectra of the plasma tail of comet Halley (1P/1982 U1) have been discovered in pure ion tail spectra ( Å , ) of comet Dl ∼ 4700-6300 l/Dl ∼ 1000-4400 Hyakutake (C/1996 B2) and three other recent comets (Nakamura-Nishimura-Machholz P/1994 N1, Austin C/1989 X1, and Brorsen-Metcalf 32P/1989 N1), but not in comet Hale-Bopp (C/1995 O1). The strengths of the bands near 4940, 5310, and 6000 Å are correlated among the comets observed, indicative that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…We compared our tail spectrum of de Vico with the list of identified and unidentified species in the spectrum of the tail of comet C/1996 B2 (Hyakutake) (Wyckoff et al 1999). Some of Wyckoff et al's H 2 O + lines are seen in our spectra, while others are not, and we detect many H 2 O + lines that they did not see (however, our data are at much higher spectral resolution and so exact matches in wavelength with their identifications are difficult).…”
Section: Line Identificationsmentioning
confidence: 99%
“…We compared our tail spectrum of de Vico with the list of identified and unidentified species in the spectrum of the tail of comet C/1996 B2 (Hyakutake) (Wyckoff et al 1999). Some of Wyckoff et al's H 2 O + lines are seen in our spectra, while others are not, and we detect many H 2 O + lines that they did not see (however, our data are at much higher spectral resolution and so exact matches in wavelength with their identifications are difficult).…”
Section: Line Identificationsmentioning
confidence: 99%
“…In 1999, Wyckoff et al [1] reported spectroscopic observations of the comets Halley, Hyakutake, and Hale-Bopp. They detected several unassigned molecular emission bands in the plasma tails of the comets.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, it became possible to establish the fact that such unidentified emissions belong to the radiation of comet ions. This is evidenced by the profiles of unidentified emissions obtained by several authors, including (Arpigny 1995;Wyckoff et al 1999). At the same time, until recently, a great number of unidentified emissions has been considered as the radiation from unknown sources.…”
Section: Introductionmentioning
confidence: 94%